Sagittal sinus thrombosis associated with thrombocytopenia: A report of two patients - (:unkn) unknown (ELSEVIER SCIENCE INC, 1999)
Reported are two patients presenting with both thrombocytopenia and sagittal sinus thrombosis. The first patient is a 42-month-old male with no identified thrombophilic risk factors who developed acute neurologic symptoms after an acute infection. The second patient is a 22-month-old female with no history of preceding infection but had a positive lupus anticoagulant test. She also developed deep venous thrombosis and was treated with intravenous heparin, Both patients are currently doing well without neurologic deficits. To the authors knowledge the second patient is the youngest reported patient with cerebral vein thrombosis associated with thrombocytopenia and lupus anticoagulant, These observations carl attention to the need for a thorough investigation of thrombophilic risk factors in pediatric patients with thrombotic complications. (C) 1999 by Elsevier Science Inc. All rights reserved.
Keywords: CEREBRAL VENOUS THROMBOSIS; ANTIPHOSPHOLIPID SYNDROME; ANTIBODIES; PURPURA